2022
DOI: 10.3390/info13050234
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach for Repairing Missing Activity Labels in Event Logs for Process Mining

Abstract: Process mining is a relatively new subject that builds a bridge between traditional process modeling and data mining. Process discovery is one of the most critical parts of process mining, which aims at discovering process models automatically from event logs. Like other data mining techniques, the performance of existing process discovery algorithms can be affected when there are missing activity labels in event logs. In this paper, we assume that the control-flow information in event logs could be useful in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In [19], a novel classification event imputation method is proposed, which can recover missing categorical events by learning structural features observed in the event log. In [20], an LSTM-based prediction model that uses the prefix and suffix sequences of events with missing activity labels as input to predict the missing labels is proposed, demonstrating high repair capability. In [21], the BERT4Log model and weak behavior profile theory, combined with a multi-layer multi-head attention mechanism is introduced, for interpretable repair of low-quality event logs.…”
Section: A Attribute-level Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…In [19], a novel classification event imputation method is proposed, which can recover missing categorical events by learning structural features observed in the event log. In [20], an LSTM-based prediction model that uses the prefix and suffix sequences of events with missing activity labels as input to predict the missing labels is proposed, demonstrating high repair capability. In [21], the BERT4Log model and weak behavior profile theory, combined with a multi-layer multi-head attention mechanism is introduced, for interpretable repair of low-quality event logs.…”
Section: A Attribute-level Repairmentioning
confidence: 99%
“…F1: Deterministic repair for known anomalies or missing attributes, where the position of the anomaly or missing attribute is clearly identified. Attribute-level repair [13], [17], [19], [20] ✓ ✓…”
Section: Summary Of Existing Workmentioning
confidence: 99%
“…This review identifies research gaps and proposes a research agenda for its application in various business contexts. Chen et al [13] observed that process mining bridges process modelling and data mining. To propose an LSTM-based model to repair missing activity labels in event logs, outperforming existing methods.…”
Section: Related Workmentioning
confidence: 99%
“…Bayesian networks are a class of probabilistic graphical models that can be applied to repair an event log with missing timestamps [14] and missing events [15,16]. Additionally, long short-term memory (LSTM) is an artificial neural network in deep learning, able to predict the missing event and activity labels in event logs [17]. Another technology enabling the resolution of missing data issues is likelihood-based algorithms, i.e., single imputation by event relationship (SIER) and multiple imputation by event chain (MIEC), which are able to repair event logs with missing events, timestamps, and resources [18].…”
Section: A Review Of Event Log Preprocessing Techniquesmentioning
confidence: 99%
“…It should be noted that several previously mentioned approaches from the artificial intelligence, machine learning, and deep learning category are able to partly recover missing data. However, these techniques utilize external reference models, i.e., process models defined based on pre-existing process knowledge, and align the incomplete event log according to the expected behavior [15][16][17].…”
Section: A Review Of Event Log Preprocessing Techniquesmentioning
confidence: 99%